THE IMPACT OF PROGRAMMED LEARNING STRATEGY USING EDUCATIONAL MEANS (AUDIO-VISUAL) IN LEARNING SOME VOLLEYBALL SKILLS FOR STUDENTS - Dr. Hazem Ali Ghazl (Galaxy International Interdisciplinary Research Journal, 2023)
The most prominent characteristic of our contemporary world is that change and development in all aspects of life and in all fields, especially the field of teaching, since the teaching profession is the main pillar for learning all sciences by following and using the teacher to everything new that serves the educational process. The search for modern strategies and methods that have a fundamental role in learning outcomes and simulate the capabilities and capabilities of students and make them search and think about how to perform what is required of them. For students, the current study aimed to identify the effect of the programmed learning strategy using educational means in learning the skill of defending the court and blocking the wall in volleyball for students and the importance of the study to identify the effect of the programmed learning strategy using educational audio-visual means to learn the skills of defense and blocking the wall in the volleyball game for students. It is represented by students of the second stage of the College of Physical Education and Sports Sciences / University of Al-Qadisiyah, whose number is (145). The study sample was (40), divided into two groups, with (20) students for each group. After applying the educational curriculum, which is in the educational frameworks for each skill, post-tests were conducted, and then the study results were extracted by conducting statistical transactions and discussing the results of the researcher’s mechanism. To learn the skills of defending the court and blocking the volleyball wall.